2017
DOI: 10.22159/ajpcr.2017.v10i11.20554
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Profile and Antibiotic Sensitivity Pattern of Hospitalacquired Septicemia in a Tertiary Care Hospital in North East India

Abstract: Objective: The objective of this study was to determine the bacterial agents responsible for hospital acquired septicemia and to determine the antibiotic sensitivity profile of the bacterial isolates. Methods:A total of 350 hospitalized cases clinically suspected to have hospital acquired septicemia were included in this cross-sectional observational study over a period of 1 year. Blood samples were collected for culture with aseptic precautions following universal precautions. Antimicrobial susceptibility tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
1
4
4
Order By: Relevance
“…A similar study carried out somewhere else by Ahsan et al 24 and Annamalei et al, 3 also yielded the same results where they observed >75% resistance to colistin. In the present study, it was found that CONS showed the highest resistance to Benzylpenicillin (84.4%), Erythromycin (69.2%) and Oxacillin (58.8%), which was observed to be similar to the results obtained from studies carried out by Mohanty et al, 10 (75%) and Khosravi et al, 26 (70.6%) showing high resistance to Penicillin.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A similar study carried out somewhere else by Ahsan et al 24 and Annamalei et al, 3 also yielded the same results where they observed >75% resistance to colistin. In the present study, it was found that CONS showed the highest resistance to Benzylpenicillin (84.4%), Erythromycin (69.2%) and Oxacillin (58.8%), which was observed to be similar to the results obtained from studies carried out by Mohanty et al, 10 (75%) and Khosravi et al, 26 (70.6%) showing high resistance to Penicillin.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, it is essential to find the susceptibility pattern of the antibiotic among sepsis patients. 10 A total of 28 antibiotics were tested for susceptibility in the study population for various organisms, out of which 23 antibiotics showed >50% resistance. In the study, Klebsiella pneumonia was found to be highly resistant to Tigecycline (68.5%), Ceftriaxone (60.3%), Amoxicillin/Clavulanic Acid (58.9%), Piperacillin/ Tazobactam (53.4%) and Ciprofloxacin (52.1%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But for that purpose, the clinicians must know about the antimicrobial resistance pattern of common pathogens causing sepsis. The prevalence of causative organisms of sepsis differs from region to region 15 . The surveillance of pathogens isolated from blood cultures in a hospital will help in determining the organisms causing bloodstream infections in different clinical disciplines.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they impose a heavy cost on hospitals causing increased hospitalization time, increased morbidity, and mortality. [ 4 5 ] A bacteriological culture to isolate the offending pathogens remains the mainstay of definite diagnosis of septicemia. It takes a minimum of 2–3 days to finalize the culture report and start the appropriate therapy.…”
Section: Introductionmentioning
confidence: 99%